2022
DOI: 10.3390/fi14100295
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Organization and Implementation of E-Learning in Wartime Inside Ukraine

Abstract: The article provides a factual foundation for the possibility of organizing and implementing e-learning in Ukrainian higher educational institutions during the war. The current research topicality is supported by the urgent need for training experience, organization and implementation during wartime because of the fact that both the educational process and the opportunity to obtain an education should not be halted. The study’s goal is to assess the current state of the e-learning organization and implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…At the same time, the pandemic has demonstrated that ERT is a viable contingency plan for unexpected educational emergencies. Unexpected educational emergencies (ranging from war-torn societies [112,113] to regions blighted by natural disasters [114]) are powerful examples of why continued research into ERT is crucial, as educational technologies could be a means of providing education where conventional methods are limited. Exploring and understanding ways to optimize ERT to ensure the best possible learning outcomes, regardless of the circumstances, is thus vital.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the pandemic has demonstrated that ERT is a viable contingency plan for unexpected educational emergencies. Unexpected educational emergencies (ranging from war-torn societies [112,113] to regions blighted by natural disasters [114]) are powerful examples of why continued research into ERT is crucial, as educational technologies could be a means of providing education where conventional methods are limited. Exploring and understanding ways to optimize ERT to ensure the best possible learning outcomes, regardless of the circumstances, is thus vital.…”
Section: Discussionmentioning
confidence: 99%
“…Студенти перебувають в різних містах України, навіть в окупаційних територіях в перші місяці активних бойових дій, а деякі поза межами країни, що створювало певні незручності з організацією навчального процесу, в які входять: відмінності в часових поясах, різний час введення комендантської години та режиму світломаскування (залежить від ситуації в області та щільності обстрілів населених пунктів), необхідність поєднувати навчання з роботою чи волонтерською діяльністю, тощо [10]. Вирішенням вищенаведених проблем стало проведення індивідуальних занять зі студентами з пропущених тем, постійна інформаційна підтримка через меседжери та поглиблене самостійне опрацювання тем з подальшим контролем якості підготовки викладачами кафедри [11,12].…”
Section: вступunclassified
“…Scholars (e.g. Akinde & Adetimirin, 2017;Asubiojo & Ajayi, 2017;Eze et al, 2018;Gupta et al, 2022;Hailye, 2020;Matviichuk et al, 2022;Ouma, 2021;Semlambo et al, 2022) have related ICT teaching facilities and e-learning implementation. The studies above revealed that ICT teaching facilities are important in the implementation of e-learning.…”
Section: Tangible Resources and Implementation Of E-learningmentioning
confidence: 99%